An introduction to management science quantitative approaches to decision making - Anderson, David R. (South-Western Cengage Learning, 2011)
Offers a grounding in management science techniques with a readable presentation style and examples drawn from a variety of businesses throughout the world. This title helps students learn the techniques and refine their problem solving skills with realistic problems that continue to set this established leader apart.